Environmental conditions and vascular cambium regulate carbon allocation to xylem growth in deciduous oaks. (14th November 2016) - Pérez‐de‐Lis, Gonzalo; Olano, José Miguel; Rozas, Vicente; Rossi, Sergio; Vázquez‐Ruiz, Rosa Ana; García‐González, Ignacio
Summary: Environmental conditions and the structure of the dormant cambium are assumed to affect seasonal patterns of cambial activity, hence controlling allocation of non‐structural carbohydrates (NSC) to growth. However, seasonal dynamics of xylogenesis, and their connections with NSC content and dormant cambium size, have been rarely assessed along an environmental gradient. We monitored xylogenesis and leaf phenology during 2012 and 2013, and NSC in 2012, for the drought‐sensitive Quercus robur and the drought‐tolerant Quercus pyrenaica along a water‐availability gradient in the north‐western Iberian Peninsula, and analysed dependencies of xylem production and phenology on the number of cells in dormant cambium. Study oak species showed comparable seasonal fluctuations in cambial activity and NSC content, despite Q. pyrenaica had a shorter growing season and a lower wood production than Q. robur . A sharp drop in spring NSC levels at all study sites evidenced that stored carbohydrates were crucial for earlywood formation. Under drier conditions, both species extended the growing period in spring and autumn, but reduced and even stopped xylogenesis in summer, showing an enhanced NSC accumulation before dormancy. A higher number of cells in dormant cambium of large dominant oaks accounted for their wider xylem increments and longer active periods. Our study demonstrates that xylogenesis is modulated by predisposing effects of dormant cambium size on xylem production and growing season length. Moreover, the high plasticity of cambial activity in deciduous oaks would confer resistance against recurrent summer drought through the improvement of the NSC status. A lay summary is available for this article. Abstract : Lay Summary